2018
DOI: 10.1016/j.jor.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fondaparinux on wound drainage after total hip and knee arthroplasty

Abstract: Fondaparinux is an effective drug for VTE prophylaxis in total joint arthroplasty with wound drainage and LOS comparable to historical controls of enoxaparin, warfarin, and rivaroxaban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The Weiss method was used to calculate wound drainage; the surgical wound was dry in 83% of patients receiving aspirin and 77% of patients who received enoxaparin on day 5 post-surgery (15). Another research found that by day 5 after surgery, the wounds of 83% of patients treated with 2.5 mg of fondaparinux were dry (16). Our results revealed that the surgical wounds of 90% of patients who were given 1.5 mg fondaparinux were dry on day 5 post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The Weiss method was used to calculate wound drainage; the surgical wound was dry in 83% of patients receiving aspirin and 77% of patients who received enoxaparin on day 5 post-surgery (15). Another research found that by day 5 after surgery, the wounds of 83% of patients treated with 2.5 mg of fondaparinux were dry (16). Our results revealed that the surgical wounds of 90% of patients who were given 1.5 mg fondaparinux were dry on day 5 post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Anti-coagulation therapies used include warfarin, enoxaparin (low molecular weight heparin), fondaparinux, rivaroxaban and aspirin to mitigate the risk of venous thromboembolic events (VTE). 4 , 31 Each of the agents have different mechanisms of actions, dosages and routes of administration, with negative and positive attributes regarding their uses that need to be considered in VTE prophylaxis. Peri-operative VTE can be catastrophic but so too can deep and superficial wound complications, therefore risk stratification is needed to balance anti-coagulation peri-operatively, and patients requiring therapeutic anti-coagulation need to be counselled about the risk regarding wound complications and infection.…”
Section: Risk Factorsmentioning
confidence: 99%
“… 11 Jones et al 34 showed that the use of LMWH and the use of aspirin resulted in a 4.92 and 3.64 times greater increase in wound discharge respectively when compared to the use of no pharmacological thromboprophylaxis. Lum et al 31 proposed that prolonged wound drainage due to anti-coagulation had a positive correlation with increased length of stay (LOS) in hospital. This was supported by Patel et al, 4 therefore using LOS as a surrogate for wound drainage assists in comparing anti-coagulation agents.…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations